DOES BREASTFEEDING DURATION INFLUENCE FAMILY FOOD INSECURITY?. (18th May 2018) - Wong, Peter; Moodie, Rosemary; Dai, David; Maguire, Jonathon; Birken, Catherine; Parkin, Patricia; Borkhoff, Cory
Abstract: BACKGROUND: Across all demographics, families without consistent access to adequate food place children at health risk. Consequences may persist beyond early life into adulthood. Public policy positions breastfeeding, the ideal nutrition for infants, as an important solution to reducing family food insecurity (FFI). However, few studies have investigated the association between breastfeeding duration and FFI. OBJECTIVES: To evaluate the association between total breastfeeding duration and FFI in Canadian urban children. DESIGN/METHODS: A cross-sectional study was conducted of children aged 0–2 years, from a practice-based child research network. Total breastfeeding duration was collected from parent-reported questionnaires. FFI was measured using 2-item food insecurity and validated 1-item NutriSTEP screens. Multivariable regression analysis was performed adjusting for pre-specified covariates. RESULTS: Among 3838 children, the mean total breastfeeding duration was 10.6 months (SD=6.7). Families with food insecurity (14.7%) had increased odds of younger mothers, more males and older and more children. In adjusted model, breastfeeding duration was not associated with FFI (OR 0.99; 95% CI 0.98, 1.01). Low-income families were 9 times more likely to be family food insecure than high-income families (p=0.00). CONCLUSION: Contrary to public policy, our study found no association between breastfeeding and family food insecurity (FFI). However, other factors may predominate, in particular family income and structure. Given the detrimental impact of FFI, further research is needed to understand the role of infant feeding practices within the larger political, policy and cultural framework.